2016
DOI: 10.1063/1.4946845
|View full text |Cite
|
Sign up to set email alerts
|

Generation of continuous wave terahertz frequency radiation from metal-organic chemical vapour deposition grown Fe-doped InGaAs and InGaAsP

Abstract: Abstract-We demonstrate the generation of continuous wave terahertz (THz) frequency radiation from photomixers fabricated on both Fe-doped InGaAs and Fe-doped InGaAsP, grown by metal-organic chemical vapor deposition. The photomixers were excited using a pair of distributed Bragg reflector (DBR) lasers with emission around 1550 nm, and THz radiation was emitted over a bandwidth of greater than 2.4 THz. Two InGaAs and four InGaAsP wafers with different Fe doping concentrations were investigated, with the InGaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The fabrication procedure was the same as described in ref [4]. The NSGs consisted of 100-nm-wide metal lines with a 200 nm pitch, and are identical to those of references [1] and [2], which are reported to provide enhanced absorption for both 780 nm and 1550 nm optical radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication procedure was the same as described in ref [4]. The NSGs consisted of 100-nm-wide metal lines with a 200 nm pitch, and are identical to those of references [1] and [2], which are reported to provide enhanced absorption for both 780 nm and 1550 nm optical radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The second parabolic mirror and detector were placed on a mechanical delay line to enable phase control and ensure the optimum path difference between the emitter and detector. The current generated in the detector was amplified using a FEMTO trans-impedance amplifier with a gain of 10 7 and measured using a lock-in amplifier [4]. Figure 2 shows the measured spectral bandwidth obtained from the SSN and DSN emitter.…”
Section: Resultsmentioning
confidence: 99%
“…Since then various publications have studied Fe-doped InGaAs as a PC material [59,60,143,148]. For instance, Wood et al [149] showed that precise control of the Fe-doping can be achieved if added during the epitaxial growth process.…”
Section: Doped Ingaasmentioning
confidence: 99%